Konsep Hidup Sejahtera Menurut Quraisy Syihab (Perspektif Maqāṣid al-Syarī’ah): The Concept of Prosperous Life According to Quraisy Syihab (Maqāṣid al-Syarī’ah Perspective) - Dewi, Erna; Khairil Fata; Badriah M. Thaib (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to analyze the general criteria that are commonly used to measure the happiness and welfare of people's lives and evaluate the conformity of the criteria with the principles of Maqāṣid al-Syarī’ah. This research uses the literature method. Data collection is carried out by compiling primary data sources and secondary data, then discussing them and analyzing the data. The results of this study show that happiness does not have to be in the form of maximizing wealth and consumption, but rather in fulfilling material and spiritual aspects that are balanced and satisfying, and still complying with the principles of Maqāṣid al-Syarī’ah law, namely namely ḥifẓu al-dīn/guarding religion, ḥifẓu al-nafs/guarding the soul, ḥifẓu al-‘aql/guarding the intellect, ḥifẓu al-māl/guarding property, and ḥifẓu al-nasl/guarding descendants. Material needs include clothing, food, board, education, and property, as well as all goods and services that guarantee comfort and happiness. Spiritual needs include obedience to God, spirituality, a happy soul, family and social harmony, and others.